Factors Influencing Sustainable Destinations: A PRISMA-based Systematic Literature Review - I Gusti Agung Sasih Gayatri; I. G. A. Ketut Giantari; Tjokorda Gde Raka Sukawati; Gede Suparna (International Journal of Social Science and Business, 2025)
The study seeks to build a holistic and evidence-based understanding of how multiple interrelated factors jointly shape sustainable tourism destinations worldwide. Scopus, Google Scholar, and ProQuest searches were used in this systematic literature review, along with a PRISMA-guided snowballing technique. 32 empirical studies published between 2016 and 2025 were found during the review. According to the findings, a complex and multifaceted combination of elements pertaining to visitors, organisation and management, social and community factors, environmental and ecological factors, and destination experiences and attractions all have an impact on sustainable destination development. Sustainability can only be attained by a combination of interconnected elements, aided by cooperation from visitors, managers, legislators, and local communities. By combining empirical data from various contexts and providing useful suggestions for enhancing destination management, policy creation, and community empowerment, this study advances theory. The synthesis offered in this review contributes significant academic value while delivering practical guidance for stakeholders seeking to design more effective and context-responsive strategies for achieving destination sustainability. Future research is suggested to adopt longitudinal and mixed-method approaches, explore simultaneous factor interactions, and expand geographical coverage to enrich global perspectives on sustainable destinations.